Pengaruh Penambahan Wijen Sangrai Terhadap Karakteristik Fisikokimia Pada Mayones Vegetarian: The Effect Of Adding Roasted Sesame On The Physicochemical Characteristics Of Vegetarian Mayonnaise - putri, raekhanrahmah; Handayani, Murni; Utami, Sari Widya; kristiningsih, ari (Politeknik Negeri Cilacap, 2024)
Mayonnaise is a mixture of oil in water with egg yolk as a binding agent. However, egg yolk and palm oil have a content that is not good for health, so other alternative ingredients are needed to make it healthier. Soybean extract and oil can replace egg yolk and palm oil as the main ingredients. Soybean extract has a